Ventilation System of HXD2B Locomotive - 任广慧 (机车电传动)
The ventilation system of high-power AC drive electrical locomotive HXD2B was introduced. Considering its uniqueness, descriptions was provided from filtering device, ventilating structure and ventilation facilities etc of locomotive ventilation system. The ventilating mode suited the particularity of the structure and controlling units of high-power AC drive electrical locomotive, and satisfied general ventilating and cooling requirement.